2012
DOI: 10.1111/j.1542-2011.2012.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and Management of Vulvar Dermatologic Conditions: Lichen Sclerosus, Lichen Planus, and Lichen Simplex Chronicus

Abstract: Lichen sclerosus, lichen planus, and lichen simplex chronicus are dermatologic conditions that can affect the vulva. Symptoms include vulvar itching, irritation, burning, and pain, which may be chronic or recurrent and can lead to significant physical discomfort and emotional distress that can affect mood and sexual relationships. With symptoms similar to common vaginal infections, women often seek care from gynecological providers and may be treated for vaginal infections without relief. Recognition and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
75
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 59 publications
(136 reference statements)
0
75
0
2
Order By: Relevance
“…12,13 Wet mount microscopy or yeast culture may reveal yeast as the cause of the scratching, 13 or an irritant or allergen may be identified based on the patient's history or skin testing.…”
Section: 13mentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Wet mount microscopy or yeast culture may reveal yeast as the cause of the scratching, 13 or an irritant or allergen may be identified based on the patient's history or skin testing.…”
Section: 13mentioning
confidence: 99%
“…[1][2][3][4] A number of factors, including the availability of over-thecounter antifungal medications, 5,6 and patient and provider time pressures and comfort with undertaking a pelvic exam, may lead to an empiric trial of therapy without undertaking a physical exam or diagnostic testing. While the most common causes of these symptoms are BV, vaginal candidiasis and vaginal trichomoniasis, 2,3 the differential diagnosis is broad, and includes vulvar infections, 7 vulvovaginal atrophy, 8,9 reactions to irritants or allergens, 10,11 inflammatory conditions, 12,13 premalignant, 14 and malignant lesions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The chief symptom is vulvar itching, which sometimes worsens at night. 2,3 Additionally, women may report cracking or bleeding of the vulvar skin and perianal area. Rarely is lichen sclerosus asymptomatic and found on routine examination.…”
Section: What Diagnoses Should Be Considered?mentioning
confidence: 99%
“…1 The most common complaint is pruritus, which is often amenable to treatment with topical steroids. 2 However, there is a subset of patients who develop vulvar pain, such that treatment with neuropathic pain medications (NPMs), such as antidepressants or anticonvulsants, is needed. 3 In a recently published retrospective chart review, we found that 83.1% of women with vulvar LS presenting for care at a tertiary referral vulvar care clinic reported vulvar pain (other than itching).…”
mentioning
confidence: 99%